Sharing and choosing within the household: A survey - Jacques Le Cacheux (University of Essex, Institute for Social and Economic Research (ISER), 2005)
This paper attempts at providing a survey of the different models of individual decision making within the household. The first section reviews the traditional approach to household decision making and emphasize its weaknesses. In addition to the standard assumption of selfish agents, other behavioral hypotheses
Keywords: D13; J1; J2; 330; caring à la Becker and altruism